1992
DOI: 10.1001/archinte.1992.00400230077013
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors During Estrogen-Norethindrone and Cholecalciferol Treatment

Abstract: The effect of cholecalciferol and estrogen-norethindrone treatment on total cholesterol level, high-density lipoprotein cholesterol level, blood pressure, and body mass index was investigated in 74 postmenopausal women in a double-blind, randomized trial. Blood pressure and body mass index did not change throughout the study. We demonstrated a decrease (11%) in serum cholesterol level after 1 year of treatment with estrogen-norethindrone. When this treatment was combined with cholecalciferol, a similar decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The current study used a double-blind, randomised, placebocontrolled design with adequate power to detect small changes in clinic and ambulatory blood pressure produced by different doses of a C21 progestogen administered in a cyclical regimen in doses spanning the usual clinical dose range combined with a fixed daily dose of oral oestrogen. The results of the current study are consistent with those of previous studies, including the PEPI study, which have found no change [2][3][4][5][6][7][8][9][10]12 or a reduction [24][25][26]29 in blood pressure associated with the addition of a progestogen to 'replacement' doses of oestrogen.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current study used a double-blind, randomised, placebocontrolled design with adequate power to detect small changes in clinic and ambulatory blood pressure produced by different doses of a C21 progestogen administered in a cyclical regimen in doses spanning the usual clinical dose range combined with a fixed daily dose of oral oestrogen. The results of the current study are consistent with those of previous studies, including the PEPI study, which have found no change [2][3][4][5][6][7][8][9][10]12 or a reduction [24][25][26]29 in blood pressure associated with the addition of a progestogen to 'replacement' doses of oestrogen.…”
Section: Discussionsupporting
confidence: 91%
“…Collectively, previous studies have variably shown no change, 1-12 a decrease 1,2,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] or an increase 4,9,11,21,[30][31][32][33][34][35] in blood pressure with various combinations of HRT. Unfortunately, few of the previous studies have been designed to differentiate between the effects on blood pressure of the individual oestrogen ('natural', conjugated equine or semisynthetic) and progestogen (C21 or C19 derivatives administered as cyclical or continuous therapy) components of the regimen when these preparations have been administered in combination.…”
Section: Introductionmentioning
confidence: 99%
“…Myrup and colleagues accompanied 74 postmenopausal healthy Danish women (>70 years) for 18 months. The protocol of supplementation with 0.5 μg of 1,25(OH)2D/day for 1 year presented no statistical significance for any of the parameters analyzed (i.e., total cholesterol (TC); high-density lipoprotein cholesterol (HDL-c); blood pressure at 0, 3, 6, 9, 12, and 18 months) [ 51 ]. On the other hand, a study of 463 postmenopausal women (45–75 years; mean age 58 years) showed that women with low 25(OH)D levels (<30 ng/mL) had higher levels of TC ( p = 0.031), triglycerides (OR 1.55, 95%CI = 1.13–2.35), and HDL-c (OR 1.60, 95%CI = 1.19–2.40) [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among them, one study met all our inclusion criteria but could not be incorporated into the meta-analysis because it reported quartiles instead of variance [12]. 5 more trials were excluded because vitamin D was a part of mixed intervention [13-17]. Other 4 studies were not included because they focused on the hemodialysis patients [18-21].…”
Section: Resultsmentioning
confidence: 99%